Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

$z_1 = 1+i$ is a given solution.

I guess what I have to find is $z_2$ and $z_3$ in

$(z - (1 + i))(z - z_2)(z-z_3) = z^3 - (b+6) z^2 + 8 b^2 z - 7+b^2$.

I tried to divide the polynomial by $(z - (1 + i))$, but that didn’t seem to work because of the $b$. According to the Complex conjugate root theorem $z_2 = \overline{z_1} = 1 - i$ is a solution too and somebody mentioned that it’s a hint that all coefficients are real. But I still don’t know how to proceed. What am I missing?

share|cite|improve this question
If $1+i$ is a root of your cubic, then $1-i$ ought to be a root of your cubic as well if it is to have real coefficients. This means your cubic can be written as $$(z-(1+i))(z-(1-i))(z-x)=(z-x)(z^2-2z+2)$$ Expand out and compare coefficients. – J. M. May 13 '12 at 8:35
More explicitly, consider $$\frac{z^3-(b+6)z^2+8b^2 z+b^2-7}{z^2-2z+2}=z-b-4+\frac{(b+1)(2(4b-5)z+b+1)}{z^2-2 z+2}$$... now, what $b$ can I use so that nasty rational expression at the far right zeroes out? – J. M. May 13 '12 at 8:48
If $z_{1}=1+i$ and $z_{2}=1-i$, since the independent term is $% -7+b^{2}=-\left( 1+i\right) \left( 1-i\right) z_{3}=-2z_{3}$ it would imply that $z_{3}=\frac{7-b^{2}}{2}$. However there is no $b$ such that the given cubic $z^{3}-(b+6)z^{2}+8b^{3}z-7+b^{2}=0$ thas these 3 solutions. Is there any typo? – Américo Tavares May 13 '12 at 10:19
It’s $b^2$ instead of $b^3$. – Lenar Hoyt May 13 '12 at 10:27
@mcb Thanks! I posted an answer. – Américo Tavares May 13 '12 at 11:04
up vote 5 down vote accepted

Consider the cubic polynomial $$\begin{equation*} P(z)=z^{3}+Az^{2}+Bz+C \end{equation*}\tag{1},$$ where the coefficients $A,B$ and $C$ are real numbers. If we denote its roots by $z_{1},z_{2}$ and $z_{3}$, then it factors as $$\begin{eqnarray*} P(z) &=&\left( z-z_{1}\right) \left( z-z_{2}\right) (z-z_{3}) \\ &=&z^{3}-\left( z_{1}+z_{3}+z_{2}\right) z^{2}+\left( z_{1}z_{2}+z_{2}z_{3}+z_{1}z_{3}\right) z-z_{1}z_{2}z_{3}. \end{eqnarray*}\tag{2}$$ The constant term is $$\begin{equation*} P(0)=C=-z_{1}z_{2}z_{3} \end{equation*}.$$ In the present case $A=-(b+6)$, $B=8b^{2}$ and $C=-7+b^{2}$. Since $z_{1}=1+i$ is a given solution, then $z_{2}=\overline{z}_{1}=\overline{1+i}=1-i$ is another solution, as you concluded. We thus have $z_{1}z_{2}=\left( 1+i\right) \left( 1-i\right)=2$ and $$\begin{equation*} -7+b^{2}=-2z_{3} \end{equation*}\tag{3},$$ whose solution is

$$\begin{equation*} z_{3}=\frac{7-b^{2}}{2}. \end{equation*}\tag{4}$$

Since $P(z_1)=P(z_2)=0$, we have $$\begin{eqnarray*} &&\left( 1+i\right) ^{3}-(b+6)\left( 1+i\right) ^{2}+8b^{2}\left( 1+i\right) -7+b^{2} \\ &=&-9+9b^{2}+i\left( -10-2b+8b^{2}\right)=0, \end{eqnarray*}\tag{5}$$

$$\begin{eqnarray*} &&\left( 1-i\right) ^{3}-(b+6)\left( 1-i\right) ^{2}+8b^{2}\left( 1-i\right) -7+b^{2} \\ &=&-9+9b^{2}+i\left( 10+2b-8b^{2}\right)=0, \end{eqnarray*}\tag{6}$$

which means that $b$ satisfies the system $$\begin{equation*} \left\{ \begin{array}{c} -9+9b^{2}=0 \\ 10+2b-8b^{2}=0. \end{array} \right. \end{equation*}\tag{7}$$ The solution of $(7)$ is $b=-1$. Using $(4)$ we find $$z_{3}=3.\tag{8}$$

share|cite|improve this answer

You have two unknowns here, the third root which we call $r$, and the variable $b$ in your equation. You can find two equations in these two unknowns to solve for both $r$ and $b$.

First, the $z^2$ coefficient is always $-1$ times the sum of the roots, so you have $$b + 6 = (1 + i) + (1 - i) + r = 2 + r$$ This reduces to $r = b + 4$. Next, the the constant term is equal to $(-1)^3$ times the product of the roots, so you have $$b^2 - 7 = -(1 + i)(1-i)r = -2r$$ You now can solve these two equations for $b$ and $r$. I substitute $r = b + 4$ in the last equation, and get $$b^2 - 7 = -2b - 8$$ This reduces to the quadratic equation $b^2 + 2b + 1 = 0$, which is solved only by $b = -1$. Then $r = b+ 4 = 3$ is your remaining root.

share|cite|improve this answer
Vieta is a nice thing... – J. M. May 13 '12 at 14:15

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.